When Equivalence is Not Enough: Translation Adjustments of Philosophical Text in Comic Form - Karjo, Clara Herlina (Bina Nusantara University, 2013)
The tenet of good translation is to achieve idiomatic equivalence. However, when the translation work is going to be published, there should be some adjustments, either lexical or structural. The reasons for adjustment might be various: for politeness, conciseness, etc. This article discusses the translation adjustments of a Chinese philosophical book: The Sayings of Zhuang Zi by comparing the original translation by the translator with the published book which has been edited by publisher’s editor. The objectives of this study are to find different types of translation adjustment made by the editor and to analyze the possible reasons for the adjustment.